2021
DOI: 10.1016/j.ekir.2020.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Trial of Acute Changes in Plasma Phosphate After Phosphorus-Standardized Meals in Peritoneal Dialysis

Abstract: Introduction Hyperphosphatemia is associated with increased morbidity and mortality in patients with chronic kidney disease. The aim of this study was to assess whether a meal with high phosphorus content would affect plasma phosphate in the hours that follow among subjects with end-stage kidney disease on peritoneal dialysis. Methods This was a single-blinded randomized cross-over trial of 12 subjects on maintenance peritoneal dialysis, in which subjects were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a recent study by Lundin et al . in 12 HD patients, a meal with high phosphorus content did not significantly affect plasma phosphate compared to a meal with low phosphorus content 47 . Isakova et al .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In a recent study by Lundin et al . in 12 HD patients, a meal with high phosphorus content did not significantly affect plasma phosphate compared to a meal with low phosphorus content 47 . Isakova et al .…”
Section: Discussionmentioning
confidence: 72%
“…There are a limited number of small studies in this field. In a recent study by Lundin et al in 12 HD patients, a meal with high phosphorus content did not significantly affect plasma phosphate compared to a meal with low phosphorus content 47 . Isakova et al examined the difference between 2 whole-food meals of 250 mg and 500 mg of phosphorus content in 13 patients with CKD stage 3 to 4, and observed that serum phosphate decreased after both meals.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We recognize that phosphorus levels may change before or after meals. However, a recent study found that a high phosphorus meal only has a negligible effect on plasma phosphate compared to low phosphorus meal in PD patients [ 22 ]. Additionally, we did not have information on D/P creatinine ratio at baseline and end of study in all participants.…”
Section: Discussionmentioning
confidence: 99%